2009
DOI: 10.1068/b33042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of city size, shape, and form, and neighborhood size and shape in agent-based models of residential segregation: are Schelling-style preference effects robust?

Abstract: In 1971 Thomas Schelling outlined a model in which group segregation emerged out of the residential decisions of individual agents who were guided by relatively weak preferences for same-group contact, preferences that on first consideration appeared to be compatible with integration (Schelling, 1971). This agent-based model has proven to be an important tool in the study of segregation dynamics and the role of individual preferences in producing patterns of segregation. Rigorous formal studies (Young, 1998;Zh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 13 publications
1
36
0
3
Order By: Relevance
“…3 Schelling concluded that small preferences for similarity can lead to massive segregation. This conclusion is quite robust across many changes to the model, including different utility functions (Zhang 2004;Bruch and Mare 2006;Pancs and Vriend 2007), different rules for updating (Bruch and Mare 2006), differing neighborhood sizes, and different spatial configurations (Fossett and Dietrich 2009). These studies show that it is extremely hard to avoid segregation when agents have some preference for like neighbors.…”
Section: Schelling's Models Of Segregation Thomas Schelling Famouslymentioning
confidence: 66%
“…3 Schelling concluded that small preferences for similarity can lead to massive segregation. This conclusion is quite robust across many changes to the model, including different utility functions (Zhang 2004;Bruch and Mare 2006;Pancs and Vriend 2007), different rules for updating (Bruch and Mare 2006), differing neighborhood sizes, and different spatial configurations (Fossett and Dietrich 2009). These studies show that it is extremely hard to avoid segregation when agents have some preference for like neighbors.…”
Section: Schelling's Models Of Segregation Thomas Schelling Famouslymentioning
confidence: 66%
“…Dado el carácter material de los métodos computacionales empleados para la aproximación a los fenómenos complejos, la comprensión computacional también depende de los avances en materia ingenieril. Varias de las extensiones con las que se ha mostrado la robustez del mecanismo subyacente de asimetría espacial del modelo de Schelling hacen uso de modelos en donde hay una representación espacial con alto nivel de realismo [28]. Generar estas representaciones, sin embargo, requirió inicialmente de un avance ingenieril en términos del desarrollo de sistemas híbridos que combinan modelos basados en agentes y sistemas de información geográfica [29].…”
Section: ¿Dónde Están Los Patrones?unclassified
“…No es claro de qué forma, ni hasta qué punto, diferentes métodos puedan capturar las intuiciones y creencias más importantes sobre la ontología de fenómenos sociales complejos. El modelo de Schelling, por ejemplo, es un autómata celular cuyos resultados han sido confirmados por diferentes replicaciones y extensiones que han incluido una cantidad mucho mayor de información empírica [28], [32]. Si bien el modelo original es extremadamente sencillo, esútil porque captura el mecanismo subyacente de asimetría espacial, que es el mismo con el que operan modelos mucho más robustos e intricados de segregación espacial.…”
Section: ¿Cómo Se Modelan Los Patrones?unclassified
“…After the publication of Schelling's model, several studies (see e.g. Fossett and Dietrich, 2009, Pancs and Vriend, 2007, and Zhang, 2004 have documented the robustness of Schelling's result across a wide range of modifications in his model (e.g. think of changes in neighbourhood sizes, spatial configurations, and individuals' tolerance thresholds for individuals of a different type).…”
Section: Schelling's Checkerboard Modelmentioning
confidence: 99%